Use of C-reactive protein to tailor antibiotic use: a systematic review and meta-analysis. Issue 12 (22nd December 2018) - Petel, Dara; Winters, Nicholas; Gore, Genevieve C; Papenburg, Jesse; Beltempo, Marc; Lacroix, Jacques; Fontela, Patricia S
Abstract : Background and objectives: C-reactive protein (CRP) has been proposed to guide the use of antibiotics. However, study results are controversial regarding the benefits of such a strategy. We synthesised the evidence of CRP-based algorithms on antibiotic treatment initiation and on antibiotic treatment duration in adults, children and neonates, as well as their safety profile. Design: Systematic review and meta-analysis. Data sources: MEDLINE, EMBASE, CENTRAL and CINAHL from inception to 20 July 2017. Eligibility criteria for selecting studies: We included randomised controlled trials (RCTs), non-RCTs and cohort studies (prospective or retrospective) investigating CRP-guided antibiotic use in adults, children and neonates with bacterial infection. Data extraction and synthesis: Two researchers independently screened all identified studies and retrieved the data. Outcomes were duration of antibiotic use, antibiotic initiation, mortality, infection relapse and hospitalisation. We assessed the quality of the included studies using the Cochrane Collaboration's tool (RCTs), and A Cochrane Risk Of Bias Assessment Tool: for Non-Randomized Studies of Interventions and the Newcastle-Ottawa scale (non-RCTs). We analysed our results using descriptive statistics and random effects models. Results: Of 11 165 studies screened, 15 were included. In five RCTs in adult outpatients, the risk difference for antibiotic treatment initiation in the CRP group was −7% (95% CI: −10% to –4%), with no difference in hospitalisation rate. In neonates, CRP-based algorithms shortened antibiotic treatment duration by −1.45 days (95% CI −2.61 to –0.28) in two RCTs, and by −1.15 days (95% CI −2.06 to –0.24) in two cohort studies, with no differences in mortality or infection relapse. Conclusion: The use of CRP-based algorithms seems to reduce antibiotic treatment duration in neonates, as well as to decrease antibiotic treatment initiation in adult outpatients. However, further high-quality studies are still needed to assess safety, particularly in children outside the neonatal period. PROSPERO registration number: CRD42016038622